Ethical and Theological Responses to Climate Change - Purwanto, Edi; Kristiawan, Sonya (STT Pelita Dunia, 2025)
This study explores the ethical and theological responses to climate change, particularly at the intersection of anthropocentrism and eco-theology. Using a Systematic Literature Review (SLR), the research investigates how theological perspectives guide ethical actions in climate change mitigation, with a specific focus on the Indonesian context. The findings highlight the central roles of stewardship and justice in religious responses. Indonesian Christian, Islamic, and indigenous spiritual traditions offer unique frameworks for addressing environmental challenges, thereby enriching the global discourse on climate ethics. The study also underscores the global significance of theological contributions to climate ethics, advocating for the integration of moral responsibility and environmental justice into climate policies and actions. In doing so, it provides insights into the potential of religious institutions and theological reflections to bolster climate action, both locally and globally.